Spoiled brats : stories - Rich, Simon (Little, Brown and Company, 2014)
"A collection of stories culled from the front lines of the millennial culture wars. Rife with failing rock bands, student loans, and participation trophies, [this book] is about a generation of narcissists--and the well-meaning boomers who made them that way"-- Amazon.com.